Consideration of Opioid Agonist Treatment in A Pregnant Adolescent: A Case Report and Literature Review. Issue 2 (April 2020) - Spada, Meredith; Kmiec, Julie; Glance, Jody B.; Gopalan, Priya
Background: Opioid use greatly increases the risk of overdose death, as well as contracting human immunodeficiency virus (HIV) and hepatitis. Opioid agonist treatment is recommended for pregnant women who are dependent on opioids. However, there is a dearth of studies on the use of opioid agonist treatment in pregnant teenagers. Case: Ms. A, a 15 year-old G1PO in foster care, presented to our tertiary women's hospital requesting opioid agonist treatment for use of pill opioids. She reported nasal inhalation of 5–6 opioid tablets daily, with recent attempts to self-taper using nonprescribed buprenorphine since learning of her pregnancy. Last reported opioid use was >24 hours prior to admission. Urine drug testing was positive only for opioids (negative for buprenorphine and methadone). She did not exhibit significant withdrawal symptoms while hospitalized. The psychiatric treatment team recommended deferring opioid agonist treatment and pursuing outpatient substance use treatment. Unfortunately, Ms. A did not attend outpatient treatment and was lost to follow up. Discussion: Based upon our experience and review of the studies regarding opioid use disorder (OUD) and perinatal and adolescent opioid use, we recommend that pregnant adolescents with OUD be referred to opioid agonist treatment with buprenorphine or methadone. Studies specifically addressing opioid agonist treatment in pregnant teenagers are needed.